Correlates of Social Engagement in Nursing Home Residents with Dementia - Hyunwook Kang, PhD, RN (Elsevier, 2012)
Purpose: The social needs of nursing home (NH) residents with dementia are often ignored even though they are capable of expressing their emotions and responding in social interactions. Insufficient social engagement in this population is known to be associated with low quality of life as well as many negative health outcomes, such as mortality, agitation, and functional decline. The purpose of this study was to identify the correlates of social engagement in NH residents with dementia. Methods: The study used a descriptive, correlational design. A total of 153 older adults with dementia in 17 Iowa NHs participated in this study. Minimum Data Set for NH version 2.0 served as an outcome measure to evaluate social engagement, cognitive and physical functions, depression, and behavioral symptoms. Demographic data were obtained from the participants' medical records. Results: The findings indicated that no significant relationship was found between demographic characteristics and social engagement. There were significant and negative correlations between the degree of social engagement and the levels of cognitive impairment, activities of daily living impairment, depression, and vision. Among these correlates, depression was the most potent predictor of engagement. Conclusion: The study provided information about the correlates of social engagement in NH residents with dementia. Future research needs to be conducted to develop nursing interventions to involve these individuals in social activities tailored to functional levels, and depression in more diverse geographic regions.